Citra Diri Para Tokoh Pemerintah Dalam Cerpen Asy-Syarr Al-Ma’būd Karya Najib Machfuzh - Hanifa, Shaniasofi Zarra; Farhah, Eva (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This study was conducted with the aim of examining the self-image of government figures contained in the text of the short story A'sy-Syarru al-Ma'bud by Najib Machfudz. The self-image is revealed by using a qualitative descriptive method by utilizing the concept of self-image theory from Jonathon D. Brown. The research technique was carried out by means of library techniques, recording and classifying data in accordance with the formulation of the problem discussed, namely how the self-image of government figures is presented in this short story. The results of this study show that the self-image of government figures, namely, the character of Judge Sumar is found based on physical aspects imaged as a male character, based on social aspects imaged as a judge and based on psychological aspects imaged as hardworking, honest, determined and responsible. The image of Police Officer Ram based on physical aspects is portrayed as a male character, based on social aspects is portrayed as a policeman and based on psychological aspects is portrayed as hardworking, honest, determined and responsible. Doctor Chatib's image is portrayed as a male character, based on social aspects he is portrayed as a doctor and based on psychological aspects he is portrayed as hardworking, honest, determined and responsible.